Case report: A comprehensive report on the first confirmed Mpox case in the Philippines during the 2022 Mpox global outbreak: from clinical presentation to shotgun metagenomic sequencing analysis - Ylaya, Edward Matthew; Grande, Phoebe Grace; Dancel, Lei Lanna; Nicolasora, Amalea Dulcene; Polotan, Francisco Gerardo; Pantoni, Roslind Anne; Melo, Ezekiel; Ortia, Stephen Paul; Manalo, Joanna Ina; Abulencia, Miguel Francisco; Chu, Maria Yna Joyce; Dizon, Timothy John; et al. (Frontiers in Medicine, 2024)
We report a case of a 31-year-old Filipino male with travel history to several European countries in July 2022. He developed five non-tender, well-defined, umbilicated pustules with erythematous borders on the upper lip, left gluteal area, bilateral knees, and left ankle. Skin punch biopsy findings were suggestive of a viral infection. Mpox infection from Clade II (previously known as the West African clade) was confirmed by detecting and amplifying the G2R_G, G2R_WA and C3L gene targets using qPCR. Shotgun metagenomic sequencing subsequently identified a Mpox genome sequence belonging to B.1.3 lineage of Clade IIb, associated with the current multi-country outbreak. Serologic varicella IgM test was positive but varicella PCR of the skin lesion and metagenomic sequencing did not indicate the presence of the varicella virus. The patient was discharged and continued isolation at home until all scabs had completely fallen off. The presence of pustules among patients with risk factors such as possible close physical contact with infected individuals in areas with reported cases of Mpox should raise suspicion for such an infection. Establishment and optimization of qPCR protocol were necessary to confirm Mpox infection. Metagenomic sequencing successfully characterized the etiologic agent of the first laboratory-confirmed Mpox case in the Philippines belonging to Clade IIb which is mainly responsible for the 2022 Mpox global outbreak.